Re-reading Philippine history - Solmerano, Ernesto Thaddeus M. (Fastbooks Educational Supply, Inc., 2019)
"The book analyzes Philippine history from multiple perspectives through the lens of selected primary sources coming from various disciplines and of different genres. The end goal is to develop the historical and critical consciousness of the students so that they will become versatile, articulate, broad-minded, morally upright and responsible citizens. This book also includes mandatory topics on the Philippine Constitution, agrarian reform and taxation."--Provided by publisher.